Exergy Analysis Of Jatropha And Microalgal Biodiesel Production Plants - Kotey, Cynthia (2011)
Estimates of crude oil reserves show that its exhaustion will occur in 2047 at a rate of 83 million barrels per day compared to an extraction rate of approximately 98 million barrels/day in 2010. As a result of this, present research and developments are geared towards sustainable production of liquid biofuels especially biodiesel to replace fossil based liquid fuel in the near future. In this study, thermodynamic performance parameters of jatropha methyl ester (JME) and microalgae methyl ester (MME) production plants are determined and compared.